Bedside-measurement of serum cholinesterase activity predicts patient morbidity and length of the intensive care unit stay following major traumatic injury - Aleksandar R. Zivkovic (Nature Portfolio, 2019)
Abstract Major traumatic injury (MTI), a life-threatening condition requiring prompt medical intervention, is associated with an extensive inflammatory response often resulting in multiple organ dysfunction. Early stratification of trauma severity and the corresponding inflammation may help optimize resources at the intensive care unit (ICU). The cholinergic system counters inflammation by quickly modulating the immune response. Serum cholinesterase (butyrylcholinesterase, BChE) is an enzyme that hydrolyses acetylcholine. We tested whether a change in the BChE activity correlates with the morbidity and the length of ICU stay. Blood samples from 10 healthy volunteers and 44 patients with MTI were gathered at hospital admission, followed by measurements 12, 24 and 48 hours later. Point-of-care approach was used to determine the BChE activity. Disease severity was assessed by clinical scoring performed within 24 hours following hospital admission. BChE activity, measured at hospital admission, showed a significant and sustained reduction and correlated with disease severity scores obtained 24 hours following admission. BChE activity, obtained at hospital admission, correlated with the length of ICU stay. Bedside measurement of BChE activity, as a complementary addition to established procedures, might prove useful in the primary assessment of the disease severity and might therefore optimize therapy in the ICU.